Madura Language Jargon in the Beach Area of Pamekasan - Ria Kasanova; Muhammad Darrin Zuhri (SELL Journal : Scope of English Language Teaching, Linguistics, and Literature, 2018)
Pamekasan beach area is very varieties in forms of language. They used more than one various form. This jargon used to make simple when they speak or interact each other. Thus it is clear that the language is not monolithic, not only in one form, but in various forms. Languages that are still within the scope of the same language system (langue) are called language variants. The phenomenon of language other than can be observed as a phenomenon of system or language structure can be observed as a social phenomenon. As a social phenomenon, the use of language in society is influence for understanding in what they speak or what they purpose. In relation to the above matter in this study the researchers further study it through the title of research "Madura language Jargon in the beach area of pamekasan)". Descriptive qualitative method is the method of this research. Analyzing the data by describing the words or sentences based on the the category and after that deciding the conlusion. In this research the techniques are, first, Techniques of data collection, for grouping the technique by focus on the research. and second, Technique of data anaysis. Based on data analysis, it can be concluded that the use of Madura language jargon in the beach area of pamekasan of is quite a lot, this can be proved by the existence of some words that is fifty three of nouns, thirty one of verbs, and thirty four of adjectives. The conclusion is the jargon often used in the beach area, especially in Pamekasan. Because they used a simple word or sentence in their daily activities. For them, they used it for making simple or easy to understand in the communication.